1981
DOI: 10.1111/j.1432-1033.1981.tb05334.x
|View full text |Cite
|
Sign up to set email alerts
|

Complementation in vitro between Purified Mutant Fatty Acid Synthetase Complexes of Yeast

Abstract: 1. By dissociation and subsequent reassociation of appropriate pairs of mutant fatty acid synthetases, hybrid multienzyme complexes were obtained whose overall fatty acid synthetase activities were restored to a considerable extent. The complementation thus achieved in vitro could be both intragenic and intergenic and was, in all cases studied, in agreement with the known complementation characteristics of fatty acid synthetase cr;l.c)2. Similarly, the method of reversible dissociation could be used to reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…β‐ketoacyl synthase, β‐ketoacyl reductase or pantetheine‐binding. In heteroallelic crosses, fas2‐mutants with different functional lesions complement each other while those being defective in the same function do not [18,22]. As an exception, complementation between isofunctionally defective fas2‐mutants is observed with a few specific allele combinations.…”
Section: Resultsmentioning
confidence: 99%
“…β‐ketoacyl synthase, β‐ketoacyl reductase or pantetheine‐binding. In heteroallelic crosses, fas2‐mutants with different functional lesions complement each other while those being defective in the same function do not [18,22]. As an exception, complementation between isofunctionally defective fas2‐mutants is observed with a few specific allele combinations.…”
Section: Resultsmentioning
confidence: 99%
“…The intermediate resolution x-ray structures of fungal and mammalian FAS reveal large distances among chain extension and chain-modifying domains, suggesting great conformational flexibility for the ACP to mediate synthesis of the growing fatty acid. Similarly, biochemical experiments show that the ACPs of fungal and mammalian FASs interact with more than one catalytic chamber (31,32). In the case of NorS, the SAT domain in PksA selects the appropriate acyl length from the associated FAS subunits to divert NorS from fatty acid to polyketide synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic complementation studies with yeast mutants which were specifically defective in one of the various FAS domains revealed that overall FAS activity was always restored, both in vitro and in vivo, whenever two mutations which affected two different catalytic activities were combined (74,140,178). For complementation, it was irrelevant whether the affected domains were located on the same or on two different subunits (140,178). Thus, every catalytic site of yeast FAS is obviously capable of interacting with any other site, at least within an ␣ 2 ␤ 2 FAS subcomplex.…”
Section: Negative Cooperativitymentioning
confidence: 99%
“…Determining the molar amounts of substrate bound per mole of enzyme, Even though the individual ␣␤ monomer of yeast FAS is possibly capable of palmitic acid synthesis, cooperation between both identical and nonidentical subunits within the ␣ 6 ␤ 6 oligomer has in fact been demonstrated. Genetic complementation studies with yeast mutants which were specifically defective in one of the various FAS domains revealed that overall FAS activity was always restored, both in vitro and in vivo, whenever two mutations which affected two different catalytic activities were combined (74,140,178). For complementation, it was irrelevant whether the affected domains were located on the same or on two different subunits (140,178).…”
Section: Negative Cooperativitymentioning
confidence: 99%